Blijde inkomst z 1356 roku, czyli brabancka Wielka Karta Wolności - Strobel, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The Brabant charter of rights and liberties Blijde inkomst of 1356 — the most important contract charter in the history of estate monarchy in the Netherlands, the parties to which were the Brabant royal couple and the Brabant higher estates — was probably modelled on the Magna Charta Libertatum. The principles enshrined in the Blijde inkomst, e.g. of the integrity of the territory of the duchy and of the binding nature of the provisions of law with regard to the rulers, survived in the collective memory for centuries, eventually leading to the emergence of Belgium as a separate state.
Keywords: Blijde inkomst / Radosne wejście; rok 1356; Księstwo Brabancji; Joanna, księżna Brabancji; Wacław, I książę Luksemburga; Karta Kortenberga